Check Point NG : next generation security administration - Simonis, Drew (Syngress Publishing, 2002)
Unparalleled security management that IT professionals have been waiting for.Check Point Software Technologies is the worldwide leader in securing the Internet. The company's Secure Virtual Network (SVN) architecture provides the infrastructure that enables secure and reliable Internet communications. CheckPoint recently announced a ground-breaking user interface that meets the computer industry's Internet security requirements. The Next Generation User Interface is easy to use and offers unparalleled security management capabilities by creating a visual picture of security operations.